2010
DOI: 10.1186/1748-7161-5-25
|View full text |Cite
|
Sign up to set email alerts
|

SpineCor treatment for Juvenile Idiopathic Scoliosis: SOSORT award 2010 winner

Abstract: IntroductionJuvenile idiopathic scoliosis is a condition used to describe patients who are least 4 years of age but younger than 10 when the deformity is first identified. In these patients, the condition is usually progressive and those that are diagnosed at five years or younger have a high chance of progression to a large curve, with additional pulmonary and cardiac complications. The main form of conservative treatment for juvenile scoliosis is the use of a bracing system. This prospective interventional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 16 publications
0
33
0
2
Order By: Relevance
“…• Soft Bracing (SB) : it includes mainly the SpineCor brace [ 102 , 103 ], but also other similar designs [ 104 , 105 ]…”
Section: Evidence-based Clinical Practice Approach To Idiopathic Scolmentioning
confidence: 99%
“…• Soft Bracing (SB) : it includes mainly the SpineCor brace [ 102 , 103 ], but also other similar designs [ 104 , 105 ]…”
Section: Evidence-based Clinical Practice Approach To Idiopathic Scolmentioning
confidence: 99%
“…Juvenile scoliosis: Juvenile scoliosis develops at the age of 4-10 years and comprises 10-15 % of all idiopathic scoliosis in children [14], untreated curves may cause serious cardiopulmonary complications, and curves of 30°and more tend to progress, 95 % of these patients need a surgical procedure [14].…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Coillard et al, a 2-year follow-up after treatment completion demonstrated curvature stabilisation in 95.7% of patients. Moreover, 10% of the patients in that group demonstrated further spontaneous correction of scoliosis [17].…”
Section: Discussionmentioning
confidence: 91%
“…w 2-let nim okre sie ob serwa cji od mo men tu za koń cze nia le cze nia u 95,7% cho rych wy ka za no sta bi li za cję skrzy wie nia. Po nad to u 10% cho rych w tej gru pie wy ka za no dal szą sponta nicz ną ko rek cję skrzy wie nia [17].…”
Section: Discussionunclassified